Feasibility Study of Correcting Circuit Scheme for Automatic Control System of Total Air in Boiler - V. I. Nazarov; A. L. Burov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper contains results of investigations on dynamic characteristics automatic control system (ACS) for total air consumption (TAC) in a boiler with corrections for О2 and СО. From transition process point of view the ACS TAC with correction for СО is considered as the most optimum one as with disturbance attack on fuel expenditure so discharging beyond boiler furnace.